Preparation method and application of flexible self-supporting lithium-sulfur battery interlayer material
The three-dimensional porous network structure modified by Co/CoSe2 heterostructure is prepared by electrospinning and in-situ selenization as the intermediate layer material of lithium sulfur batteries, which solves the problem of performance degradation in lithium sulfur batteries due to changes in sulfur volume and diffusion of lithium polysulfide in lithium sulfur batteries. , achieving a significant improvement in electrochemical performance.
Patent Information
- Application Number
- CN202411543089.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-10-31
AI Technical Summary
During the charging and discharging process, lithium-sulfur batteries have reduced battery performance and cycle life due to changes in the volume of sulfur and the diffusion of lithium polysulfide, and the modification effect of existing carbon-based intermediate layer materials is not ideal.
Electrospinning and in-situ selenization methods were used to prepare a three-dimensional porous network structure composed of self-supporting carbon nanofibers and in-situ grown carbon nanotubes as the intermediate layer material of lithium sulfur batteries.
Through chemical anchoring and catalytic conversion, the shuttle effect is suppressed, the redox kinetics are improved, and the shuttle of polysulfides is physically blocked, which significantly improves the electrochemical performance of lithium-sulfur batteries.
Smart Images

Figure CN119481364A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of lithium-sulfur batteries, and in particular to a preparation method and application of a flexible self-supporting lithium-sulfur battery intermediate layer material. Background Art
[0002] Lithium-sulfur batteries use metallic lithium as the negative electrode and elemental sulfur as the positive electrode. Their theoretical energy density is as high as 2600 Wh / kg, which far exceeds that of traditional lithium-ion batteries. This shows great application potential in electric vehicles, portable electronic devices, and large-scale energy storage systems. From a resource perspective, sulfur is abundant in the earth's crust, inexpensive, and environmentally friendly, which provides cost advantages and resource guarantees for the large-scale production of lithium-sulfur batteries.
[0003] However, lithium-sulfur batteries face many challenges in their actual development. For example, during the charge and discharge process, the sulfur in the positive electrode undergoes complex multi-step electrochemical reactions to produce lithium polysulfide intermediates that are easily soluble in the electrolyte. These lithium polysulfides easily diffuse inside the battery, resulting in the so-called "shuttle effect", which not only causes the loss of active materials, but also causes the battery's self-discharge phenomenon to intensify, thereby reducing the battery's coulombic efficiency and cycle life. In addition, sulfur undergoes a large volume change during the charge and discharge process, which may destroy the integrity of the electrode structure and thus affect the battery's performance and stability.
[0004] Research has found that the introduction of a functional intermediate layer in lithium-sulfur batteries can improve the electrochemical performance of lithium-sulfur batteries and effectively block the migration of polysulfides, thereby improving the utilization rate of sulfur. Carbon-based intermediate layers have attracted attention due to their high conductivity and physical blocking of polysulfides, but such carbon-based materials do not have outstanding adsorption capacity for polysulfides. For this reason, researchers use polar materials to modify carbon-based materials, such as metal oxides, metal sulfides, metal nitrides and transition metals, but the current modification of carbon-based materials is still not ideal for improving the electrochemical performance of lithium-sulfur batteries.
[0005] Therefore, developing an intermediate layer material that can effectively improve the electrochemical performance of lithium-sulfur batteries is of great significance to the development of lithium-sulfur batteries. Summary of the invention
[0006] In order to improve the electrochemical performance of lithium-sulfur batteries, the present application provides a preparation method and application of a flexible self-supporting lithium-sulfur battery intermediate layer material.
[0007] In a first aspect, the present application provides a method for preparing a flexible self-supporting lithium-sulfur battery intermediate layer material, using the following technical solution: A method for preparing a flexible self-supporting lithium-sulfur battery intermediate layer material, which comprises a three-dimensional porous network structure composed of self-supporting carbon nanofibers modified with Co / CoSe2 heterostructures and in-situ grown carbon nanotubes obtained by electrospinning and in-situ selenization.
[0008] By adopting the above technical scheme, the Co / CoSe2 heterostructure is used as a chemical adsorption carrier and electrocatalyst, inhibiting the shuttle effect through chemical anchoring, and accelerating the redox kinetics of LiPSs through catalysis; the three-dimensional porous conductive network of CNF-CNT obtained by electrospinning has a physical barrier effect on the shuttle of polysulfides. Therefore, this high conductivity, high specific surface area material combined with the heterostructure realizes the chemical anchoring and catalytic conversion of lithium polysulfide, so that the prepared lithium-sulfur battery has good electrochemical performance; at the same time, the preparation method of this application is simple, low cost, environmentally friendly, and has good application prospects.
[0009] In a specific implementation scheme, the following steps are included: (1) dissolving polyacrylonitrile (PAN) and cobalt acetate in N,N-dimethylformamide (DMF) to prepare a spinning solution, electrospinning the spinning solution and drying it to obtain a fiber membrane; (2) Dissolve dimethylimidazole in a methanol solution, stir until the solution is clear, add the fiber membrane, wash with deionized water and ethanol, and then dry to obtain an intermediate; then pre-oxidize, carbonize and selenize the intermediate to obtain a three-dimensional porous conductive intermediate layer material Co / CoSe2@CNF-CNT.
[0010] By adopting the above technical scheme, the Co / CoSe2@CNF-CNT intermediate layer material prepared by electrospinning process and in-situ selenization method can not only be used as the second current collector to enhance conductivity and reduce interface impedance, but also increase specific surface area and provide more active sites. The three-dimensional porous conductive network of CNF-CNT in the Co / CoSe2@CNF-CNT intermediate layer material has a good physical barrier effect on polysulfides. At the same time, the Co / CoSe2 heterogeneous structure catalyst can promote the physical adsorption of polysulfides, accelerate the catalytic conversion of polysulfides, promote the deposition of Li2S, and improve the redox kinetics.
[0011] In addition, the formation of CNTs in the preparation method of the composite material is because Co has a high catalytic activity and can promote the in-situ growth of CNTs. It is not deposited by the CVD method. Therefore, the preparation method is simple, has a high yield, low cost, good repeatability, and is environmentally friendly. It has a good application prospect and is of great significance to the development of lithium-sulfur batteries.
[0012] In a specific embodiment, in step (1), the mass molar ratio of polyacrylonitrile to cobalt acetate is 1 g: (1-3) mmol; and the mass volume ratio of polyacrylonitrile to N,N-dimethylformamide is 1 g: (5-15) ml.
[0013] By adopting the above technical scheme, polyacrylonitrile and cobalt acetate are dissolved in N,N-dimethylformamide to form a spinning solution, and the spinning solution is electrospun to obtain a fiber membrane (CH3COO)2Co@PAN; by optimizing the addition amounts of the three, the loading rate of polyacrylonitrile on the catalyst cobalt acetate is higher, and the formed (CH3COO)2Co@PAN has better stability.
[0014] In a specific embodiment, in step (1), the electrospinning parameters are as follows: temperature is 25-35°C, relative humidity is 40-50%, positive high voltage is 10-20 kV, negative high voltage is -1--3 kV, the receiver is a stainless steel plate, the distance between the needle and the stainless steel plate is 14-16 cm, and the propulsion speed is 0.7-0.8 mL h -1 .
[0015] By adopting the above technical scheme, the solvent evaporation rate and the sensitivity of the solution to humidity are greatly affected by the ambient temperature and humidity during the electrospinning process. In normal indoor air, higher relative humidity will lead to a decrease in fiber diameter. Air is mainly composed of water vapor, nitrogen, oxygen and carbon dioxide. These molecules can interact or react with electrospinning materials. The effect of humidity on fiber diameter depends on the interaction between the solution and the surrounding water vapor. Temperature changes the average diameter of nanofibers through two opposing effects: increasing the evaporation rate of the solvent and reducing the viscosity of the solution. As the temperature increases, the diameter of the fiber decreases. However, both the increased solvent evaporation and the reduced solution viscosity are adaptive mechanisms that lead to a decrease in the average fiber diameter.
[0016] The spinning voltage range is 10-20kV, and the prepared nanofibers are continuous and have a smooth surface. As the spinning voltage increases, the diameter of the nanofibers decreases. When the spinning voltage is low, the electric field force is small and it is difficult to overcome the surface tension of the spinning solution itself, which hinders the stretching and splitting of the spinning solution, so that the diameter of the formed nanofibers is larger. As the spinning voltage gradually increases, the electric field strength becomes stronger and stronger, and the polymer solution jet is more likely to stretch and split, forming nanofibers with a thinner diameter. When the spinning voltage is too high, the electric field strength is too high, resulting in an increase in the jet volume of the spinning solution each time, and the jet speed is accelerated, which is not conducive to the stretching and splitting of the jet, thereby increasing the fiber diameter and worsening the uniformity, resulting in the formation of beaded or beaded nanofibers. Therefore, nanofibers of suitable diameter can be obtained by controlling the voltage during spinning.
[0017] By controlling the propulsion speed during spinning, not only the production efficiency of the nanofibers can be effectively controlled, but more importantly, it will affect the stability of the needle droplet and the diameter of the fiber; in the process of preparing nanofibers, as the spinning speed increases, the diameter of the prepared nanofibers will gradually increase due to the incomplete drying of the nanofiber jet during the flight between the needle tip and the receiver, and even lead to the formation of beaded fibers.
[0018] The distance between the spinning needle and the receiver affects the electric field strength and the volatilization of the spinning solution solvent, thereby affecting the diameter of the nanofiber. If the voltage remains constant, the electric field strength is inversely proportional to the distance. In this electrospinning device, the distance range is 14-16 cm, which allows the solvent to evaporate for a sufficient flight time to deposit a dry fiber bundle; if the distance is too short, the solvent will not evaporate sufficiently, and fused fibers may be formed.
[0019] In a specific embodiment, in step (1), the drying is performed under vacuum at 55-65° C. and kept warm for 10-14 hours.
[0020] By adopting the above technical solution, vacuum drying is a common method to remove moisture from the material. The temperature and time during drying have a crucial impact on the performance of the product. When the drying temperature is too high, the insulation time is short, which has a certain impact on the pore size of the fiber membrane; on the contrary, when the drying temperature is too low, the insulation time is long, the water is not evaporated enough, and the subsequent reaction effect is affected.
[0021] In a specific embodiment, in step (2), the molar ratio of dimethylimidazole to cobalt acetate is 1:2-6.
[0022] By adopting the above technical scheme, the N atoms in the imidazole structure can coordinate with the metal cobalt ions, affecting the pore size and pore structure of the intermediate layer material. The N atoms in the imidazole can also increase the nitrogen content of the intermediate layer material and increase its specific capacitance. Therefore, by optimizing the molar ratio of dimethylimidazole to cobalt acetate, the intermediate layer material obtained has good chemical stability, which can improve the electrochemical performance of the lithium-sulfur battery.
[0023] In a specific embodiment, in step (2), the pre-oxidation is specifically: keeping the intermediate at 230° C. for 2 h at a heating rate of 1° C. / min in air.
[0024] By adopting the above technical scheme, the intermediate is pre-oxidized to remove the oxygen groups in PAN, so that CNFs have stronger mechanical stability.
[0025] In a specific implementation scheme, in step (2), the carbonization treatment is specifically: heating the pre-oxidation treated material to 900° C. in argon and carbonizing for 3 hours.
[0026] By adopting the above technical solution, argon is an inert gas that does not react with most materials including metals; at the same time, it is used at high temperatures without any risk of reaction; the use of argon can protect metal Co from oxidation and ensure the integrity and quality of metal Co.
[0027] In a specific implementation scheme, in step (2), the selenization treatment is specifically as follows: selenium powder is added on top of the carbonized material, heated to 450° C. in argon gas and kept at this temperature for 2 hours, and then naturally cooled to room temperature.
[0028] By adopting the above technical scheme, during the selenization treatment, the material surface is flat and the particles are uniform and dense by directly heating the temperature to 450°C and keeping it warm for 2 hours. By placing selenium powder on the top of the material and heating it for selenization, when the temperature of the selenium source reaches the melting point, the surface selenium powder melts into liquid and then diffuses to the carbonized layer at the bottom. The reaction between the carbonized layer and the selenium source is a solid-liquid reaction. The reaction first occurs on the contact surface between the carbonized layer and the selenium powder. The reaction interface moves toward the preset inner layer over time until the reaction ends. The chemical reaction is quickly completed at the interface, and the diffusion of the selenium element is controllable. According to the area and thickness of the intermediate layer material, an appropriate amount of selenium powder is covered on the surface of the carbonized material as a selenium source, thereby greatly saving raw materials and avoiding contamination by selenium vapor.
[0029] In a second aspect, the present application provides a lithium-sulfur battery, which adopts the following technical solution: A lithium-sulfur battery, comprising the above-mentioned flexible self-supporting lithium-sulfur battery intermediate layer material.
[0030] By adopting the above technical solution, the flexible self-supporting lithium-sulfur battery intermediate layer material prepared in the present application can be used as an auxiliary channel for ion conduction, which can not only adjust the path of ion transmission, but also absorb electrolyte additives seeping from the positive electrode to ensure that they can be reused during the operation of the battery, thereby reducing the loss of additives. At the same time, as an intermediate layer material, it does not affect the Li + normal migration.
[0031] In summary, the present application includes at least one of the following beneficial technical effects: 1. In the present application, an electrospinning process and in-situ selenization are used to prepare a three-dimensional porous network structure composed of self-supporting carbon nanofibers modified with Co / CoSe2 heterostructures and in-situ grown carbon nanotubes as an intermediate layer material for lithium-sulfur batteries (Co / CoSe2@CNF-CNT); the Co / CoSe2 heterostructure is used as a chemical adsorption carrier and electrocatalyst to inhibit the shuttle effect through chemical anchoring and accelerate the redox kinetics of LiPSs through catalysis; the three-dimensional porous conductive network of CNF-CNT obtained by electrospinning has a physical barrier effect on the shuttling of polysulfides, thereby improving the electrochemical performance of lithium-sulfur batteries.
[0032] 2. The preparation method of the flexible self-supporting lithium-sulfur battery intermediate layer material of the present application is simple, low-cost, environmentally friendly, and has good application prospects; 3. The material obtained by directly heating the temperature to 450°C and keeping it warm for 2 hours during the selenization treatment in this application not only has a flat surface, uniform and dense particles, but also can be covered with an appropriate amount of selenium powder as a selenium source on the surface of the carbonized material according to the area and thickness of the intermediate layer material, thereby greatly saving raw materials and avoiding contamination by selenium vapor. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 This is the SEM morphology of the flexible self-supporting lithium-sulfur battery intermediate layer material prepared in Example 1.
[0034] Figure 2 This is the XRD curve of the flexible self-supporting lithium-sulfur battery intermediate layer material prepared in Example 1.
[0035] Figure 3 This is the element distribution mapping diagram of the flexible self-supporting lithium-sulfur battery intermediate layer material prepared in Example 1.
[0036] Figure 4 This is the SEM morphology of the flexible self-supporting lithium-sulfur battery intermediate layer material prepared in Comparative Example 1.
[0037] Figure 5 This is the XRD curve of the flexible self-supporting lithium-sulfur battery intermediate layer material prepared in Comparative Example 1.
[0038] Figure 6 This is the XRD curve of the flexible self-supporting lithium-sulfur battery intermediate layer material prepared in Comparative Example 2.
[0039] Figure 7 These are the test results of the cycle performance of the batteries assembled based on the prepared flexible self-supporting lithium-sulfur battery intermediate layer material at a current density of 0.5 A / g in Example 1, Comparative Example 1 and Comparative Example 2. DETAILED DESCRIPTION
[0040] The following are examples and attached Figure 1-7 This application is described in further detail. Example
[0041] Example 1 This embodiment discloses a method for preparing a flexible self-supporting lithium-sulfur battery intermediate layer material, comprising the following steps: (1) Weigh 0.5 g polyacrylonitrile (PAN, Mw = 150000) and 0.249 g cobalt acetate ((CH3COO)2Co·4H2O) and add them to 5 ml N,N-dimethylformamide (DMF), stir at room temperature for 12 h until completely dissolved, and use this as the spinning solution; the spinning solution is electrospun and then dried to obtain a fiber membrane; the electrospinning parameters are as follows: the temperature is controlled at 30 °C, the humidity is controlled at 45%, the positive high voltage is set to 15 kV, the negative high voltage is set to -2 kV, the receiver is a stainless steel plate, the distance between the needle and the receiving plate is 15 cm, and the propulsion speed is 0.75 ml / h; the drying is carried out in a vacuum drying oven at 60 °C, and the insulation time is 12 h; (2) Dissolve 0.328 g of dimethylimidazole in 50 ml of methanol solution and stir until the solution becomes clear. Soak the fiber membrane in the clear solution for 12 h, wash with deionized water and ethanol, and dry in an oven at 60 °C to obtain an intermediate. (3) The intermediate was placed in a tubular furnace and kept at 230°C for 2 h at a heating rate of 1°C / min in air to remove the oxygen groups in PAN and make CNFs have stronger mechanical stability; after pretreatment, the material was heated to 900°C in argon and carbonized for 3 h to obtain Co@CNF-CNT; Co@CNF-CNT was placed in the middle of the tubular furnace, excess selenium powder was placed upstream of the furnace and then the tubular furnace was heated to 450°C in argon at a heating rate of 5°C / min and kept warm for 2 h. After the sample was naturally cooled to room temperature, the desired flexible self-supporting lithium-sulfur battery intermediate layer material Co / CoSe2@CNF-CNT was obtained.
[0042] like Figure 1 This is the SEM image of the flexible self-supporting lithium-sulfur battery intermediate layer material Co / CoSe2@CNF-CNT. In the Co / CoSe2@CNF-CNT intermediate layer material, carbon nanotubes grow evenly on the CNF surface to form a three-dimensional porous conductive network.
[0043] like Figure 2 This is the XRD pattern of Co / CoSe2@CNF-CNT, a flexible self-supporting lithium-sulfur battery intermediate layer material, proving the successful synthesis of Co / CoSe2@CNF-CNT.
[0044] like Figure 3 This is the element distribution mapping diagram of the flexible self-supporting lithium-sulfur battery intermediate layer material Co / CoSe2@CNF-CNT, indicating that the two elements Co and Se are evenly distributed on the surface of CNFs.
[0045] This embodiment also discloses a lithium-sulfur battery, comprising the above-mentioned flexible self-supporting lithium-sulfur battery intermediate layer material.
[0046] The preparation method of the lithium-sulfur cell of this embodiment comprises the following steps: (1) After 6 g of sublimated sulfur, 3 g of Ketjen black and 1 g of polyvinylidene fluoride were fully ground and mixed, N-methylpyrrolidone (NMP) was added and ground into a uniform slurry. The slurry was then coated on a carbon-coated aluminum foil and vacuum dried at 45 °C for 24 h. The slurry was cut into discs with a diameter of 12 mm for use. The sulfur loading of each electrode was 1.1 mg. (2) The above-cut electrode pieces were used as positive electrodes, lithium metal sheets as negative electrodes, commercial Celgard 2500 separators, and flexible self-supporting lithium-sulfur battery intermediate layer materials Co / CoSe2@CNF-CNT cut to a diameter of 16 mm were assembled into CR-2032 button cells.
[0047] Example 2 This embodiment is basically the same as embodiment 1, except that, in the method for preparing a flexible self-supporting lithium-sulfur battery intermediate layer material, step (1) is as follows: 0.5 g of polyacrylonitrile (PAN, Mw=150000) and 0.125 g of cobalt acetate ((CH3COO)2Co·4H2O) are weighed and added to 2.5 ml of N,N-dimethylformamide (DMF), and stirred at room temperature for 12 h until completely dissolved to obtain a spinning solution; the spinning solution is electrospun and then dried to obtain a fiber membrane; wherein the electrospinning parameters are as follows: the temperature is controlled at 25° C., the humidity is controlled at 40%, the positive high voltage is set to 10 kV, the negative high voltage is set to -1 kV, the receiver is a stainless steel plate, the distance between the needle and the receiving plate is 14 cm, and the propulsion speed is 0.7 ml / h; and the drying is carried out in a vacuum drying oven at 55° C., and the insulation time is 10 h.
[0048] Example 3 This embodiment is basically the same as embodiment 1, except that, in the method for preparing a flexible self-supporting lithium-sulfur battery intermediate layer material, step (1) is as follows: 0.5 g of polyacrylonitrile (PAN, Mw=150000) and 0.374 g of cobalt acetate ((CH3COO)2Co·4H2O) are weighed and added to 7.5 ml of N,N-dimethylformamide (DMF), and stirred at room temperature for 12 h until completely dissolved, to obtain a spinning solution; the spinning solution is electrospun and then dried to obtain a fiber membrane; wherein the electrospinning parameters are as follows: the temperature is controlled at 35° C., the humidity is controlled at 50%, the positive high voltage is set to 20 kV, the negative high voltage is set to -3 kV, the receiver is a stainless steel plate, the distance between the needle and the receiving plate is 16 cm, and the propulsion speed is 0.8 ml / h; and the drying is carried out in a vacuum drying oven at 65° C., and the insulation time is 14 h.
[0049] Comparative Example Comparative Example 1 This comparative example discloses a method for preparing a flexible self-supporting lithium-sulfur battery intermediate layer material, comprising the following steps: (1) Weigh 0.5 g polyacrylonitrile (PAN, Mw = 150000) and 0.249 g cobalt acetate ((CH3COO)2Co·4H2O) and add them to 5 ml N,N-dimethylformamide (DMF), stir at room temperature for 12 h until completely dissolved, and use this as the spinning solution; the spinning solution is electrospun and then dried to obtain a fiber membrane; the electrospinning parameters are as follows: the temperature is controlled at 30 °C, the humidity is controlled at 45%, the positive high voltage is set to 15 kV, the negative high voltage is set to -2 kV, the receiver is a stainless steel plate, the distance between the needle and the receiving plate is 15 cm, and the propulsion speed is 0.75 ml / h; the drying is carried out in a vacuum drying oven at 60 °C, and the insulation time is 12 h; (2) Dissolve 0.328 g of dimethylimidazole in 50 ml of methanol solution and stir until the solution becomes clear. Soak the fiber membrane in the clear solution for 12 h, wash with deionized water and ethanol, and dry in an oven at 60 °C to obtain an intermediate. (3) The above intermediate was placed in a tubular furnace and kept at 230°C for 2 h at a heating rate of 1°C / min in air to remove the oxygen groups in PAN and make CNFs have stronger mechanical stability; after pretreatment, the material was heated to 900°C in argon and carbonized for 3 h to obtain the desired soft lithium-sulfur battery intermediate layer material Co@CNF-CNT.
[0050] like Figure 4 This is the SEM image of the lithium-sulfur battery intermediate layer material Co@CNF-CNT. The morphology of the Co@CNF-CNT intermediate layer material is similar to that of the Co / CoSe2@CNF-CNT intermediate layer material. Carbon nanotubes grow evenly on the CNF surface to form a three-dimensional porous conductive network.
[0051] like Figure 5 This is the XRD pattern of Co@CNF-CNT, the intermediate layer material of lithium-sulfur battery, proving the successful synthesis of Co@CNF-CNT.
[0052] Comparative Example 2 This comparative example discloses a method for preparing a flexible self-supporting lithium-sulfur battery intermediate layer material, comprising the following steps: (1) Weigh 0.5 g polyacrylonitrile (PAN, Mw = 150000) and 0.249 g cobalt acetate ((CH3COO)2Co·4H2O) and add them to 5 ml N,N-dimethylformamide (DMF), stir at room temperature for 12 h until completely dissolved, and use this as the spinning solution; the spinning solution is electrospun and then dried to obtain a fiber membrane; the electrospinning parameters are as follows: the temperature is controlled at 30 °C, the humidity is controlled at 45%, the positive high voltage is set to 15 kV, the negative high voltage is set to -2 kV, the receiver is a stainless steel plate, the distance between the needle and the receiving plate is 15 cm, and the propulsion speed is 0.75 ml / h; the drying is carried out in a vacuum drying oven at 60 °C, and the insulation time is 12 h; (2) Dissolve 0.328 g of dimethylimidazole in 50 ml of methanol solution and stir until the solution becomes clear. Soak the fiber membrane in the clear solution for 12 h, wash with deionized water and ethanol, and dry in an oven at 60 °C to obtain an intermediate. (3) The intermediate was placed in a tubular furnace and kept at 230°C for 2 h at a heating rate of 1°C / min in air to remove the oxygen groups in PAN and make CNFs have stronger mechanical stability; after pretreatment, the material was heated to 900°C in argon and carbonized for 3 h to obtain Co@CNF-CNT; Co@CNF-CNT was placed in the middle of the tubular furnace, excess selenium powder was placed upstream of the furnace and then the tubular furnace was heated to 450°C in argon at a heating rate of 5°C / min and kept for 6 h. After the sample was naturally cooled to room temperature, the desired flexible self-supporting lithium-sulfur battery intermediate layer material CoSe2@CNF-CNT was obtained.
[0053] like Figure 6 This is the SEM image of the flexible self-supporting lithium-sulfur battery intermediate layer material CoSe2@CNF-CNT. The CoSe2 nanoparticles are agglomerated and scattered on CNF, and the number of carbon nanotubes is also reduced.
[0054] Performance Testing Battery assembly: The intermediate layer materials prepared in Example 1, Comparative Example 1 and Comparative Example 2 were used respectively, the positive electrode used a lithium sulfur battery positive electrode sheet of sublimated sulfur: Ketjen black: polyvinylidene fluoride = 6:3:1, the negative electrode sheet was a lithium metal sheet, the separator was a commercial Celgard2500 separator, the electrolyte was 1 M lithium bistrifluoromethanesulfonyl imide (LiTFSI) dissolved in ethylene glycol dimethyl ether (DME) and 1,3-dioxolane (DOL) in a volume ratio of 1:1, the electrolyte additive was 2wt% LiNO3, and the electrolyte dosage for each battery was 40μL. All batteries were assembled in a glove box (H2O, O2 <0.01ppm).
[0055] Electrochemical testing: The constant current charge-discharge and rate performance tests of lithium-sulfur batteries were carried out on the Xinwei battery testing system with a voltage window of 1.8-2.7 V and charge-discharge tests were carried out at a current density of 0.5 A / g.
[0056] like Figure 7 , this figure shows the cycle performance test results of the batteries assembled based on the prepared flexible self-supporting lithium-sulfur battery intermediate layer material modified with heterostructures in Example 1, Comparative Example 1 and Comparative Example 2 at a current density of 0.5A / g. It can be seen that the lithium-sulfur battery assembled with the Co / CoSe2@CNF-CNT intermediate layer material prepared in the present application is superior to the lithium-sulfur battery assembled with the Co@CNF-CNT intermediate layer material and the CoSe2@CNF-CNT intermediate layer material in terms of specific capacity and cycle stability.
[0057] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A method for preparing a flexible self-supporting lithium-sulfur battery intermediate layer material, characterized in that: A three-dimensional porous network structure consisting of self-supporting carbon nanofibers modified with Co / CoSe2 heterostructures and in-situ grown carbon nanotubes was obtained by electrospinning and in-situ selenization.
2. The method for preparing the flexible self-supporting lithium-sulfur battery intermediate layer material according to claim 1, characterized in that: The following steps are involved: (1) dissolving polyacrylonitrile (PAN) and cobalt acetate in N,N-dimethylformamide (DMF) to prepare a spinning solution, electrospinning the spinning solution and drying it to obtain a fiber membrane; (2) Dissolve dimethylimidazole in a methanol solution, stir until the solution is clear, add the fiber membrane, wash with deionized water and ethanol, and then dry to obtain an intermediate; then pre-oxidize, carbonize and selenize the intermediate to obtain a three-dimensional porous conductive intermediate layer material Co / CoSe2@CNF-CNT.
3. The method for preparing the flexible self-supporting lithium-sulfur battery intermediate layer material according to claim 2, characterized in that: In the step (1), the mass molar ratio of polyacrylonitrile to cobalt acetate is 1 g: (1-3) mmol; and the mass volume ratio of polyacrylonitrile to N,N-dimethylformamide is 1 g: (5-15) ml.
4. The method for preparing the flexible self-supporting lithium-sulfur battery intermediate layer material according to claim 2, characterized in that: In step (1), the electrospinning parameters are as follows: temperature is 25-35°C, relative humidity is 40-50%, positive high voltage is 10-20 kV, negative high voltage is -1--3 kV, the receiver is a stainless steel plate, the distance between the needle and the stainless steel plate is 14-16 cm, and the propulsion speed is 0.7-0.8 mL h -1 .
5. The method for preparing the flexible self-supporting lithium-sulfur battery intermediate layer material according to claim 2, characterized in that: In the step (1), the drying is specifically performed by vacuum drying at a temperature of 55-65° C. and keeping the temperature for 10-14 hours.
6. The method for preparing the flexible self-supporting lithium-sulfur battery intermediate layer material according to claim 2, characterized in that: In the step (2), the molar ratio of dimethylimidazole to cobalt acetate is 1:2-6.
7. The method for preparing the flexible self-supporting lithium-sulfur battery intermediate layer material according to claim 2, characterized in that: In the step (2), the pre-oxidation is specifically: keeping the intermediate at 230° C. for 2 h at a heating rate of 1° C. / min in air.
8. The method for preparing the flexible self-supporting lithium-sulfur battery intermediate layer material according to claim 2, characterized in that: In the step (2), the carbonization treatment is specifically as follows: heating the pre-oxidized material to 900° C. in argon and carbonizing for 3 hours.
9. The method for preparing the flexible self-supporting lithium-sulfur battery intermediate layer material according to claim 2, characterized in that: In step (2), the selenization treatment is specifically as follows: selenium powder is added on top of the carbonized material, heated to 450° C. in argon gas and kept at this temperature for 2 hours, and then naturally cooled to room temperature.
10. A lithium-sulfur battery, characterized in that: The invention comprises the flexible self-supporting lithium-sulfur battery intermediate layer material as described in claims 1 to 9.
Citation Information
Patent Citations
Preparation method of ZIF8 / zinc oxide composite material for lithium-sulfur battery functional separation layer
CN110504403A
Preparation method of functional interlayer of lithium-sulfur battery with sheet structure
CN110931687A
Double-nanoparticle embedded nitrogen-doped porous carbon nanotube lithium ion battery negative electrode material and preparation method thereof
CN113097478A
Hollow multi-shell cobalt selenide modified diaphragm for lithium-sulfur battery and preparation method of hollow multi-shell cobalt selenide modified diaphragm
CN118448813A
Nitrogen-doped multi-layer porous carbon material as well as preparation method and application thereof
CN118763236A
Cited By
Carbon nanotube / oxide lithium-sulfur battery intermediate layer of vanadium atom intercalation vanadium sulfide and preparation method of carbon nanotube / oxide lithium-sulfur battery intermediate layer
CN120709517A